2022
DOI: 10.1097/hjh.0000000000003079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of long-term antihypertensive therapy on myocardial strain: a meta-analysis

Abstract: Evidence on the impact of blood pressure (BP)lowering drugs on left ventricular (LV) mechanics in hypertension is still limited. We performed a meta-analysis of speckle-tracking echocardiographic studies in order to provide a new piece of information on this topic. Methods:The PubMed, OVID-MEDLINE, and Cochrane library databases were analysed to search for articles published from the inception up to 31 October 2021. Studies were identified by using MeSH terms and crossing the following search items: 'myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, we found both groups with stable SBP control decreased GLS from phase 1 to 2 without significant difference between treatment effects. Meanwhile, no association was found between SBP reduction and GLS improvement in the above study 22 . This equivocal result could be explained by cardiac interstitial fibrosis, which develops in HHD and is associated with reduced GLS 23 .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, we found both groups with stable SBP control decreased GLS from phase 1 to 2 without significant difference between treatment effects. Meanwhile, no association was found between SBP reduction and GLS improvement in the above study 22 . This equivocal result could be explained by cardiac interstitial fibrosis, which develops in HHD and is associated with reduced GLS 23 .…”
Section: Discussionmentioning
confidence: 55%
“…A meta‐analysis research included 1140 hypertensive patients (mean age 55.4 years, 50% men, follow‐up 6–36 months) containing 8 studies demonstrated that antihypertensive treatment was associated with the improvement in GLS 22 . However, we found both groups with stable SBP control decreased GLS from phase 1 to 2 without significant difference between treatment effects.…”
Section: Discussionmentioning
confidence: 58%
“…123,124 : GLS has shown to be able to unmask systolic dysfunction undetected by conventional LVEF, 125 also in specific settings as masked hypertension 126 and non-dippig pattern 127 ; furthermore, antihypertensive treatment has shown a clear beneficial effect on LV mechanisms, leading to improvements in GLS. 128 Sarcomeric and non-sarcomeric HCMs are typically characterized by heterogeneous echocardiographic patterns of LVH, often with a normal or supernormal EF. 129 However, all components of strain are reduced in these patients.…”
Section: Ventricular Cavity Sizementioning
confidence: 99%
“…Patients with HT and asymptomatic SLVSD derive the greatest benefit from appropriate pharmacotherapy [42]. Generally, the improvement in GLS is largely related to the reduction in LVMI rather than mere BP lowering [43].…”
Section: Roc Curve For Ivsd X (At/et)mentioning
confidence: 99%